2012
DOI: 10.1177/1367877912459140
|View full text |Cite
|
Sign up to set email alerts
|

The celebritization of society and culture: Understanding the structural dynamics of celebrity culture

Abstract: In recent debates about the ever-growing prominence of celebrity in society and culture, a number of scholars have started to use the often intermingled terms celebrification and celebritization. This article contributes to these debates first by distinguishing and clearly defining both terms and especially by presenting a multidimensional conceptual model of celebritization to remedy the current one-sided approaches that obscure its theoretical and empirical complexity. Here celebrification captures the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0
23

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(156 citation statements)
references
References 48 publications
2
117
0
23
Order By: Relevance
“…Yet, the more the supposedly private persona is revealed the more 'celebrification' occurs (cf. Driessens, 2012;Turner, 2014). Issues arise when mismatches occur between the luminary's portrayed public image and their 'true colours' as it decreased participants' willingness to forgive and influenced perceived connections to the celebrity, with regards to trustworthiness and commitment (Pornpitakpan, 2003(Pornpitakpan, , 2004Xie & Peng, 2009 Other participants like Sandy indicated that the bigger the perceived mismatch the bigger the perceived betrayal.…”
Section: Celebrity-related Driversmentioning
confidence: 99%
“…Yet, the more the supposedly private persona is revealed the more 'celebrification' occurs (cf. Driessens, 2012;Turner, 2014). Issues arise when mismatches occur between the luminary's portrayed public image and their 'true colours' as it decreased participants' willingness to forgive and influenced perceived connections to the celebrity, with regards to trustworthiness and commitment (Pornpitakpan, 2003(Pornpitakpan, , 2004Xie & Peng, 2009 Other participants like Sandy indicated that the bigger the perceived mismatch the bigger the perceived betrayal.…”
Section: Celebrity-related Driversmentioning
confidence: 99%
“…In the influential 'Status Update' Alice Marwick (2013), outlines how the techniques of selfpresentation that are performed by 'micro-celebrities' -whose celebrity status is established through recognition by a niche group of people online -are at once a marketing device and a form of entrepreneurial labor, that requires them to develop an 'authentic' brand (Banet-Weiser, 2012), while Duffy (2016) notes this as a form of 'aspirational' labor. These practices operate within the expanding cultural processes of 'celebritisation', that is the way in which social and economic capital is accumulated across social fields such as politics, fashion, sport, or journalism through hierarchies of visibility that depend on media exposure (Driessens, 2013).…”
Section: Vlogging and Youtube Celebritymentioning
confidence: 99%
“…Esa necesidad del reconocimiento del grupo, encuentra hoy en la visibilidad mediática su forma más evidente y exitosa: aparecer en los medios de comunicación de masas modifica el estatus del sujeto (Driessens, 2013;Gabler, 2011;Milner, 2010 2 y Rivière, 2009). Así, cuando la persona pasa a convertirse en contenido del medio y deviene en personaje (Rivière, 2009: 9), adquiere también en esta transformación una mayor capacidad de influencia sobre la opinión pública, erigiéndose la visibilidad mediática en símbolo de estatus y prestigio.…”
Section: La Visibilidad Como Capital Simbólicounclassified
“…A esta normalización cultural del discurso de la promoción debe añadirse el imparable crecimiento de la presencia mediática y la consideración social de las celebridades (Gabler, 2011;Milner, 2010;Rivière, 2009;Marshall, 1998), que ha derivado en la extensión de valores y prácticas propias de la cultura de la fama a otros ámbitos y a una democratización en el acceso a la celebridad -o de la posibilidad de acceso-entre personas no-célebres (Driessens, 2013;Gamson, 2011). Desde la perspectiva de este trabajo, el interés que demuestran los practicantes de la microcelebridad y la marca personal por construir y mantener audiencias personales obedecería a la búsqueda de una visibilidad ubicua, entendida esta como un capital simbólico que daría acceso a otros capitales sociales y económicos, siguiendo la teoría de la economía simbólica de Bourdieu (2008).…”
Section: Introductionunclassified